Web-Based Customer Service Information System at the Taluk Kuantan PAB UPTD - Hamid, Hafizul; Hadiwandra, T.Yudi (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
UPTD PAB (Regional Technical Implementation Unit for Clean Water Supply) Taluk Kuantan is a specialized unit established to operate the drinking water supply system (SPAM - Drinking Water Supply System). However, the provision of these services is not yet supported by an effective service system, both in terms of time and security. Where each customer is required to physically visit the UPTD PAB Taluk Kuantan office to obtain official information regarding the availability of clean water, which is typically provided in written announcements. In case of any issues related to water supply, customers must either visit the office in person or directly contact the personnel through telephone. To address this issue, a information system is required that can receive customer reports and convey information to customers. Additionally, a medium is needed that can coordinate customer data, resulting in more effective reporting. The research methodology employed in this research is Research and Development. In this research, the outcome is a service website for UPTD PAB Taluk Kuantan, resulting in an information system capable of receiving customer reports and conveying information to customers. This system can subsequently coordinate customer data, leading to more effective report generation.